New excavations at the HWK EE site: Archaeology, paleoenvironment and site formation processes during late Oldowan times at Olduvai Gorge, Tanzania. Issue 120 (July 2018) - de la Torre, Ignacio; Albert, Rosa M.; Arroyo, Adrián; Macphail, Richard; McHenry, Lindsay J.; Mora, Rafael; Njau, Jackson K.; Pante, Michael C.; Rivera-Rondón, Carlos A.; Rodríguez-Cintas, Ágata; Stanistreet, Ian G.; Stollhofen, Harald; et al.
Abstract: This paper reports the results of renewed fieldwork at the HWK EE site (Olduvai Gorge, Tanzania). HWK EE is positioned across the boundary between Lower and Middle Bed II, a crucial interval for studying the emergence of the Acheulean at Olduvai Gorge. Our excavations at HWK EE have produced one of the largest collections of fossils and artefacts from any Oldowan site, distributed across several archaeological units and a large excavation surface in four separate trenches that can be stratigraphically correlated. Here we present the main stratigraphic and archaeological units and discuss site formation processes. Results show a great density of fossils and stone tools vertically through two stratigraphic intervals (Lemuta and Lower Augitic Sandstone) and laterally across an area of around 300 m 2, and highlight the confluence of biotic and abiotic agents in the formation of the assemblage. The large size and diversity of the assemblage, as well as its good preservation, qualify HWK EE as a reference site for the study of the late Oldowan at Olduvai Gorge and elsewhere in Africa. In addition, the description of the stratigraphic and archaeological sequence of HWK EE presented in this paper constitutes the foundation for further studies on hominin behavior and paleoecology in Lower and Middle Bed II.